2003
DOI: 10.1098/rsta.2003.1177
|View full text |Cite
|
Sign up to set email alerts
|

Systematic design of phononic band–gap materials and structures by topology optimization

Abstract: Phononic band-gap materials prevent elastic waves in certain frequency ranges from propagating, and they may therefore be used to generate frequency filters, as beam splitters, as sound or vibration protection devices, or as waveguides. In this work we show how topology optimization can be used to design and optimize periodic materials and structures exhibiting phononic band gaps. Firstly, we optimize infinitely periodic band-gap materials by maximizing the relative size of the band gaps. Then, finite structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
306
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 630 publications
(311 citation statements)
references
References 16 publications
4
306
0
1
Order By: Relevance
“…Multiphysics problems, where coupled analyses are required, are promising applications due to the inherent difficulties in obtaining good designs intuitively, and thus recently more research has been conducted in this area [2,3,4,5,6]. These applications, however, have mostly been restricted to problems where the multi-physics behavior is limited to the material-part of the design.…”
Section: Introductionmentioning
confidence: 99%
“…Multiphysics problems, where coupled analyses are required, are promising applications due to the inherent difficulties in obtaining good designs intuitively, and thus recently more research has been conducted in this area [2,3,4,5,6]. These applications, however, have mostly been restricted to problems where the multi-physics behavior is limited to the material-part of the design.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the post-processed structure has a performance that is very close to the optimized structure. However, recently the author's research group has applied the topology optimization to phononic and photonic crystal design (Sigmund and Jensen, 2003;Jensen and Sigmund, 2004) where structures with intricate semi-periodic patterns appear as the result of the topology optimization process. An example of the design of a nano-scale optical splitter from Borel et al (2005) is shown in Fig.1b.…”
Section: Introductionmentioning
confidence: 99%
“…The resonance peaks can be removed or reduced by including some damping, and we also found that there is no significant change of the band-gap behavior for relatively small damping. The effect of smoothing by including damping is often used in the topology optimization of band-gap structures [7].…”
Section: Free Wave Propagation and Forced Vibration In The Optimized mentioning
confidence: 99%
“…Due to a wealth of potential applications in vibration protection, noise isolation, waveguiding, etc., the study and development of bandgap rod, mass-spring, beam, grillage, disk and plate structures, in most cases by topology optimization, have attracted increasing attention in recent years, see e.g. [5,[7][8][9][10][11][12][13][14][15][16][17][18]. Elastodynamics of finite or infinite periodic 1D rod or beam structures has been studied in [6,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation